Study on hierarchies and networks in health policy for elderly people in Mexico - Vera López, Juana Isabel (2016)
It is analyzed the current situation of the health system in Mexico, in general, and specifically, in relation to the elderly population (AM, for its acronym in Spanish) by means of the organizational models, hierarchies and networks. For this, we use the neo-institutional theory based on a political approach; through this one we established the actors that make up the hierarchy levels and those that make horizontal communication networks. In the analysis we review information from governmental and health institutions, such as the National Institute of Statistics and Geography (INEGI, for its acronym in Spanish), the World Health Organization (OMS, for its acronym in Spanish), the Pan American Health Organization (OPS, for its acronym in Spanish), the National Institute of Public Health (INSP, for its acronym in Spanish), among others. This analysis provides a prospective view of health policy for AM where the trend is toward homogenization of health legislation in Latin America, increase of state participation to finance health programs, and promotion of policies to prevent health risks.